Pengaruh Logam Berat Terhadap Sifat Fisis Pemancaran Cahaya dari Bioluminisensi Kunang-kunang (Pteroptyx tener) - Melly Sarvida (Department of Physics – Universitas Negeri Padang UNP, 2013)
Heavy metal is environmental factor which influences the relative intensity of firefly light. Heavy metal in firefly body is estimated to be able to decrease the intensity of light produced. This research will discuss the influence of heavy metal toward bioluminescence reaction of firefly. It starts from the influence of heavy metal type and concentration toward intensity, inhibition coefficient and the influence of molecule weight with bioluminescence inhibition coefficient of firefly. This research is an experimental research conducted in Material Physics and Biophysics Laboratory and Chemistry Laboratory of FMIPA UNP. In this research, the measurements of wave length and light intensity are conducted toward firefly of Pteroptyx tener taken from Sungai Lareh , a district of Koto Tangah, Padang before and after being given treatment with heavy metal by using UV-Vis spectrophotometer. The Determined variables in this research is independent variables which consist of lead (Pb), copper (Cu), iron (Fe) and zinc (Zn) and heavy metal concentration is 0,5 mg/l, 1 mg/l and 2 mg/l, the dependent variables are relative intensity of firefly light and inhibition coefficient, and the control variable is type and size of firefly and solvent media used. The result of research indicates that bioluminescence relative intensity value of firefly keep declining if heavy metal concentration rises up. The decline of the biggest intensity is caused by the existence of lead (Pb), then zinc (Zn), copper (Cu), and the smallest is iron (Fe). Bioluminescence inhibition coefficient of firefly keeps declining because of the increasing of heavy metal concentration. For concentration of 0.5 mg/l , the coefficient inhibition of lead (Pb) is 1.8620M-1, zinc (Zn) is 0.6275M-1, copper (Cu) is 0.4260M-1, and the smallest is iron (Fe) which is 0.2481M-1. For concentration of 1 mg/l, the inhibition coefficient of lead (Pb) is 1.1494M-1, zinc (Zn) is 0.4269M-1, copper (Cu) is 0.3385M-1 and the smallest one is iron (Fe) which is 0.2747M-1. For concentration of 2 mg/l , the inhibition coefficient of lead (Pb) is 0.8951M-1, zinc (Zn) is 0.3269M-1, copper (Cu) is 0.2998M-1, and the smallest one is iron (Fe) which is 0.2671M-1. The biggest inhibition coefficient from bioluminescence of firefly is caused by the existence of lead (Pb), then zinc (Zn), copper (Cu), and the smallest one is iron (Fe). The biggest Inhibition coefficient value is followed by the large of heavy metal molecule weight, that is nitrate lead (PbNO3) that has the biggest molecule weight which is 269.20 g/mol, then nitrate zinc (ZnNO3) which is 127.38 g/mol, nitrate copper (CuNO3) which is 125.55 g/mol and nitrate iron (FeNO3) which is 117.86 g/mol. Keywords: Bioluminescence, Heavy Metal, Relative Intensity and Inhibition Coefficient